(untitled) (Indian Journal of Forensic Medicine & Toxicology, 2020)
Aim: To study the adverse drug reactions (ADRs) occurring with the drug use in a tertiary care hospital. Materials and Method: This observational study conducted over a period of four months (01-Nov-2015 to 29—Feb-2016). The Central Drug Standard Control Organization (CDSCO) suspect ADR forms (15) were distributed to all clinical departments personally in Kerala medical college hospital and research center, Mangode, Cherpullaserry. Regular visits were carried out twice a week for collecting data reports. They were then analyzed, compared with state data, national data, and international data. Results A total of 25 suspected Adverse Drug Reactions forms were reported during the period of four months of the study of the out patients and in patients departments of the hospital. Among all drugs NSAIDS, followed by Antimicrobials, Antipsychotics, Bronchodilators, Antihypertensive and oral hypoglycemic agent etc.. were reported to have adverse drug reactions. Most common route of adverse drug reactions was oral, followed by IV, IM, S/C, Topical and Inhalational routes. Reactions mostly seen affecting Skin, Gastrointestinal systems, Central nervous system, and Hematological system Most patients recovered from adverse events taking suitable measures like complete stopping the offending agent, or were prescribed antihistamines, steroids in addition Conclusion: Awareness about ADR reporting is still poor amongst healthcare professionals in India. The incidence and severity of Adverse Drug Reactions documented in our study are lower than those reported in other studies. NSAIDS comprise the major drug family associated with adverse drug reactions so should be rationally prescribed. Improved communication between the physicians and nurses with the pharmacovigillance centre in the hospital is suggested.